2018
DOI: 10.1002/pola.29269
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a thermally crosslinkable polyolefin from oleic acid

Abstract: A novel thermally crosslinkable polyolefin was synthesized from biorenewable oleic acid. The obtained polymer exhibited a unique structure, bearing an inner olefin moiety in the long side chain. Since thermal auto‐oxidation and crosslinking reactions occurred at the inner olefin moiety of polymer, it could be cured by heating in air. The resultant polymer exhibited good adhesion properties to various substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The unsaturated bond of these starch esters is in a different position on the chain, possibly resulting in a different reactivity. For oleic acid derivatives, it was reported that crosslinking could occur upon heating (Ohtake et al, 2018). Method 2 resulted in the highest DS, therefore, these products were investigated further.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The unsaturated bond of these starch esters is in a different position on the chain, possibly resulting in a different reactivity. For oleic acid derivatives, it was reported that crosslinking could occur upon heating (Ohtake et al, 2018). Method 2 resulted in the highest DS, therefore, these products were investigated further.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…This peak fully disappeared after UV irradiation, consistent with cross-linking having occurred. 15,22 In addition to the presence of the double bond, cross-linking can be verified by the presence of thiols at 2500 cm −1 . As the weight fraction of EG in MA-EG-MA-based films is much lower than in films with PEG-based cross-linkers, the free thiol moiety is only visible in this FTIR spectrum before UV irradiation.…”
Section: Film Characterizationmentioning
confidence: 99%
“…A very interesting study recently reported the synthesis of 8-heptadecadiene from oleic acid, and its subsequent polymerization using zirconocene complexes with methylaluminoxane catalysts, which produced isotactic and atactic polyolefins (Figure 10). The unsaturated pendant groups allowed the conduction of a further step of post-polymerization crosslink-ing [82], as well as post-polymerization chemical modifications, such as bromination, epoxidation, and cross-metathesis [83]. The catalytic conversion of unsaturated fatty acids by isomerizing carbonylation or olefin metathesis yields (ultra)long-chain AB-type monomers bearing terminal dicarboxyl, diol, or diamine groups [84].…”
Section: Linear Polymers Based On Fatty Acids or Their Ensuing Derivativesmentioning
confidence: 99%